Interaction between sex and left ventricular reverse remodeling and its association with outcomes after transcatheter aortic valve implantation - Kuneman Jurrien H; Butcher Steele C; Stassen Jan; Singh Gurpreet K; Pio Stephan M; van der Kley Frank; Marsan Nina Ajmone; Knuuti Juhani; Bax Jeroen J; Delgado Victoria (SPRINGER, 2022)
Women with severe aortic stenosis (AS) have better long-term prognosis after transcatheter aortic valve implantation (TAVI) compared to men. Whether this is caused by sex-related differences in left ventricular (LV) reverse remodeling after TAVI is unknown. Patients with severe AS who underwent transfemoral TAVI between 2007 and 2018 were selected. LV dimensions, volumes, and ejection fraction (LVEF) were assessed by transthoracic echocardiography before TAVI and at 6 and 12 months follow-up after TAVI. LV reverse remodeling was defined as the percentual LV mass index (LVMi) reduction compared to baseline. The primary outcome was all-cause mortality. A total of 459 patients (80 ± 8 years; 52% male) were included. At 6 and 12 months follow-up, both sexes showed significant reductions in LV volumes and LVMi accompanied by improvement in LVEF, without significant differences between the sexes over time. During a median follow-up of 2.8 [IQR 1.9-4.3] years, 181 (39%) patients died. Women showed better outcomes compared to men (log-rank p = 0.024). In addition, male sex was independently associated with all-cause mortality in multivariable Cox regression (HR 1.423, 95% CI 1.039-1.951, p = 0.028). No association was observed between the interaction of percentual LVMi reduction and sex with outcomes (p = 0.64). Men and women with severe AS had similar improvement in LVEF, and similar reductions in LV volumes and LVMi at 6 and 12 months after TAVI. Women showed better survival after TAVI as compared to men. The superior outcomes noted in women after TAVI are not associated with sex differences in LV reverse remodeling.[GRAPHICS].